Arsitektur Sistem Informasi Sekolah - Khoiruddin, Hafid; Triharyanto, Bayu; Putra, Erwin Kristian; Yaqin, M. Ainul (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
The design of school information systems enterprise architecture is carried out to find detailed information about school activities based on government regulatory standards. So that the existing information system in the school business is in accordance with the existing standards of the government and there will be no errors in school activities later, a research is carried out that implements TOGAF ADM as a method in building the architecture of school information systems enterprise. Then the results obtained by business architecture include PSB (Acceptance of New Students), PA (Academic Process), PS (Release of Students), MTU (Management of Administration), MSP (Management of Facilities and Infrastructure), LAB (Laboratory), and the acquisition of architecture data, application architecture and technology architecture. So it can be concluded that the TOGAF ADM Method was successfully implemented in the School Information System Architecture and the School Information System Architecture can be used as a guide in the development and development of information systems in terms of data and information management in schools.